FENOMENA HIBRIDASI SAINS DALAM KARYA SASTRA - Bayu Pramono; Redhitya Wempi Ansori (Universitas Negeri Surabaya, 2016)
This article discused abouts current issues regarding development of Indonesian literature. The developments include many things, one of which concerns the employment of creativity in literature. Instatement of literature in this era is destined to answer the challenges of the times. Literature faced with the realities of the modern world that everything must be completely reasonable (make sense). Therefore, the employment of the literary creative process not only focuses on spices romatisme life figure œwho is so sentimental and dramatic, but the employment of current literature also involves a particular scientific field. Literature connected, combined, and mixed with science in his creative process, resulting in hybridization of science in literature. Instatement of literature involving science gives the impression that the literature in his creative process not only as